2012
DOI: 10.1099/ijs.0.033720-0
|View full text |Cite
|
Sign up to set email alerts
|

Defluviitoga tunisiensis gen. nov., sp. nov., a thermophilic bacterium isolated from a mesothermic and anaerobic whey digester

Abstract: Defluviitoga tunisiensis gen. nov., sp. nov., a thermophilic bacterium isolated from a mesothermic and anaerobic whey digester T , a thermophilic, anaerobic and slightly halophilic, rod-shaped bacterium with a sheath-like outer structure (toga), was isolated from a whey digester in Tunisia. The strain's nonmotile cells measured 3-30¾1 mm and appeared singly, in pairs or as long chains. The novel strain reduced thiosulfate and elemental sulfur, but not sulfate or sulfite, into sulfide. It grew at 37-65 6C (opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(48 citation statements)
references
References 41 publications
0
42
0
3
Order By: Relevance
“…To our knowledge, this study is the first to capture a dynamic shift in relative abundance of a Thermotogae. D. tunisiensis is a primary fermenter capable of growing on microcrystalline cellulose [100], but the genome sequence of the L3 strain only encoded a GH5 cellulase [101]. The D. tunisiensis strain identified in this study encoded a GH5 cellulase but did not encode a GH48 cellulase (Additional file 13: Table S7), which was previously found to be an absolute requirement for pure culture crystalline cellulose hydrolysis in the genus Caldicellulosiruptor [102].…”
Section: Discussionmentioning
confidence: 93%
“…To our knowledge, this study is the first to capture a dynamic shift in relative abundance of a Thermotogae. D. tunisiensis is a primary fermenter capable of growing on microcrystalline cellulose [100], but the genome sequence of the L3 strain only encoded a GH5 cellulase [101]. The D. tunisiensis strain identified in this study encoded a GH5 cellulase but did not encode a GH48 cellulase (Additional file 13: Table S7), which was previously found to be an absolute requirement for pure culture crystalline cellulose hydrolysis in the genus Caldicellulosiruptor [102].…”
Section: Discussionmentioning
confidence: 93%
“…Comparison of the four biogas communities analyzed in this study revealed that the genera Defluviitoga and Halocella were highly abundant in the thermophilic BGP4. Members of both genera were described to grow at high temperatures of up to 50°C for Halocella cellulolytica [45] and 70°C for Defluviitoga tunisiensis [46]. Additionally, these organisms use a variety of carbohydrates such as cellulose, cellobiose, xylan, and xylose for acetate, CO…”
Section: Discussionmentioning
confidence: 99%
“…In the non-Fe control cultures, the relative abundances of the three other major bacterial T-RFs dominated in the bacterial T-RF assemblages at the end of the cultivation experiments. C. proteolyticus , A. mobile , and D. tunisiensis are obligately anaerobic, fermentative bacteria that utilize various carbohydrate and proteinaceous compounds for growth and also generate acetate and H 2 /CO 2 as major fermentative products, but have different substrate utilization spectra (4, 15, 17). In the control cultures, these three bacterial species may have contributed to the degradation of organic compounds in the yeast extract to produce acetate and H 2 /CO 2 , which could then be converted into CH 4 by the methanogenic archaea.…”
mentioning
confidence: 99%